Fruit quality of feijoas in response to storage temperature and treatment with 1‑methylcyclopropene - Amarante, Cassandro Vidal Talamini do; Steffens, Cristiano André; Ducroquet, Jean Pierre Henri Joseph; Sasso, Alexandre (Pesquisa Agropecuaria Brasileira, 2009)
The objectives of this work were to characterize the postharvest physiology and to evaluate the effects of temperature and treatment with 1-methylcyclopropene (1-MCP) on the postharvest quality of fruits of feijoa (Acca selowiana) accessions from the germplasm bank of Empresa de Pesquisa Agropecuária e Extensão Rural de Santa Catarina. Fruits were harvested at commercial maturity. The genotypes Brasil (accession no. 387) and Uruguai (accession no. 454) were evaluated for respiration and ethylene production at 20ºC, and respiration rates and skin color alterations at 0, 5, 10, 20, 30ºC. The genotype Brasil (accession no. 242) was evaluated for ripening at 4ºC, after treatment with 1-MCP (0, 500 and 1,500 ppb). Brasil (accession no. 387) and Uruguai (accession no. 454) exhibited a climacteric pattern, with a peak of ethylene evolution and respiration rate at the 8th and 12th days of storage at 20oC, respectively. There was no significant difference for respiration rates and ethylene evolution between these genotypes at this temperature. There was a substantial increase of respiration rate in both genotypes with the increase in temperature from 0 to 30ºC, with a metabolic coefficient of approximately 3.5. With the increase in temperature, fruits of the genotype Brasil showed the greatest change of skin green color, while fruits of the genotype Uruguai exhibited the greatest darkening of skin. Feijoa fruits of genotype Brasil (accession no. 242) had delayed ripening when treated with 1-MCP and stored at 4oC.